Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan pada PT Intra Kota Pekanbaru - Fanny Dwina Putri; Meliza Putriyanti Zifi (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
We conducted this study at PT. Intra, a transportation services provider. This research aims to assess PT. Intra City Pekanbaru's economic performance in the wake of the COVID-19 pandemic. In other words, this is the target. The author of this study analyzed the company's financial performance using a quantitative descriptive approach. This is done so that the company's financial statements from the previous year can be analyzed and used as a benchmark for the upcoming year. From a profitability ratio perspective, the company's financial performance in 2019 and 2020 is not promising, as evidenced by the decline in percentage of each ratio; however, the company's financial performance is good when compared to industry standard values. If one looks at the company's 2019 and 2020 financial performance through the lens of the overall activity ratio, it will appear to be in a poor state. It's because the firm has less control over its assets, making it harder to turn a profit. When comparing the company's financial performance in 2019 and 2020, the liquidity ratio indicates that the company is doing well and will continue to do so in 2020. This is evident when we compare the liquidity of various markets. PT Intra is solvable if we look at its financial performance in 2019 and 2020 through the lens of solvency ratios. Short-term and long-term debt from 2019 to 2020 are both secured by the company's assets and capital.